Pertanggungjawaban Pidana Pelaku yang Melakukan Tindak Pidana dalam Keadaan Tidak Sadar Diri (Trance) Menurut Perspektif Hukum Pidana Indonesia dan Hukum Pidana Islam - Muhammad Rizky Kaisar; Chepi Ali Firman Zakaria (UNISBA Press, 2023)
Abstract. This article is entitled Criminal Responsibility of Criminal Offenders in a State of Unconsciousness (Trance) According to the Perspective of Indonesian Criminal Law and Islamic Criminal Law. The method used in this paper is normative juridical methods connected with research on events that occur in society. The occurrence of crime the phenomenon of trance or in Indonesia is often known as